2016
DOI: 10.1002/pon.4303
|View full text |Cite
|
Sign up to set email alerts
|

Association between social support, functional status, and change in health-related quality of life and changes in anxiety and depression in colorectal cancer patients

Abstract: Colorectal cancer patients who have more social support, are functionally independent and have higher improvements in HRQoL may have better results in anxiety and depression at 1 year after surgery, adjusting for age, gender, location, occupation, and baseline HADS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 40 publications
10
100
3
6
Order By: Relevance
“…This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease. Furthermore, among adolescents with significant social support, the levels of resilience (Haase et al, 1999(Haase et al, , 2014Hong & Park, 2015) and HRQOL (Arabyat & Raisch, 2015;Gonzalez-Saenz de Tejada et al, 2017) are high. Illness-related distress was the most influential factor on both resilience and HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…This result corresponds to the finding reported by many existing studies that as illness-related distress increases, resilience (Fortier et al, 2013) and HRQOL (Molzon et al, 2017;Sharkey et al, 2017) decrease. Furthermore, among adolescents with significant social support, the levels of resilience (Haase et al, 1999(Haase et al, , 2014Hong & Park, 2015) and HRQOL (Arabyat & Raisch, 2015;Gonzalez-Saenz de Tejada et al, 2017) are high. Illness-related distress was the most influential factor on both resilience and HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that chronic stress interferes with immune, endocrine and neural system functions. A number of epidemiological and clinical studies have reported that chronic stress plays an essential role in cancer occurrence, development and mortality, and reducing stress may prolong survival and decrease recurrence after therapy (14)(15)(16)(17). It has been demonstrated that chronic stress can activate the HPA axis and the SNS, leading to a release of catecholamines (NE, epinephrine and dopamine), glucocorticoids and other hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and Depression were assessed with two items asking YBCS and relatives “Have you ever been told by a healthcare provider that you have anxiety?” yes/no and “Have you ever been told by a health care provider that you have depression?” yes/no. These variables were assessed because they interfere with support and communication, and better family functioning mitigates depressive symptoms among cancer patients …”
Section: Methodsmentioning
confidence: 99%
“…yes/no. These variables were assessed because they interfere with support and communication, 33,34 and better family functioning mitigates depressive symptoms among cancer patients. 35 Fear of Cancer Recurrence (YBCS only) was assessed with four items from the Concerns About Recurrence Scale (CARS) (eg, "How much time do you spend thinking about your breast cancer coming back") using a seven-point Likert scale from one "Not at all" to seven "All the time".…”
mentioning
confidence: 99%